Global existence of L2 solutions to the Zakharov equations with additive noises. (April 2022) - Tsutsumi, Yoshio
Abstract: We show the global existence of L 2 solutions for the Cauchy problem of the Zakharov equations with additive noises in one spatial dimension. For the proof, we use the argument by Colliander, Holmer and Tzirakis, which was applied to the deterministic Zakharov equations. Our proof is an extension of their proof to the problem with stochastic external forces.